Regulation of chemotaxis by the cytoplasmic domain of tissue factor - Siegbahn, Agneta; Johnell, Matilda; Sorensen, Brit B.; Petersen, Lars C.; Heldin, Carl-Henrik (Thrombosis and Haemostasis, 2005)
We previously demonstrated that FVIIa bound to tissue factor (TF) induces a hyperchemotactic response towards PDGF-BB. The aim of the present study was to investigate the role of the cytoplasmic domain of TF in cell migration. Porcine aortic endothelial (PAE) cells expressing human PDGF β -receptors (PAE/ PDGFR β ) were transfected for expression of human wildtype TF (PAE/PDGFRβ ,TF), a construct lacking the cytoplasmic domain (PAE/PDGFRβ ,TF ∆ cyto), a construct with alanine replacement of serine 258 (PAE/PDGFRβ ,TFS258A), or a construct with alanine replacement of serine 253, 258 and 263 in the cytoplasmic domain (PAE/PDGFRβ ,TF3SA). All stably transfected cell lines expressed functional TF. Chemotaxis was analyzed in a modified Boyden chamber assay. PAE/PDGFRβ ,TF cells stinulated with FVIIa migrated towards a 100-fold lower concentration of PDGF-BB than in the absence of FVIIa,however,hyperchemotaxis was not seen in PAE/PDGFRβ ,TF ∆ cyto cells. PAE/ PDGFR β /TFS258A and PAE/PDGFRβ ,TF3SA cells responded to low levels of PDGF-BB, but migrated a significantly shorter distance than PAE/PDGFRβ ,TF cells. Thus, hyperchemotaxis towards PDGF-BB is likely to depend in part on phosphorylation of the cytoplasmic domain of TF.We conclude that the cytoplasmic domain of TF plays a pivotal role in modulating cellular migration response.Our results suggest that the FVIIa/TF complex mediates intracellular signaling by alternative signal transduction pathway(s).
Keywords: Tissue factor; platelet-derived growth factor; intracellular signaling; cell migration